The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpls.2020.580576
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function Studies of CYC/TB1-Like Genes in the Asymmetric Flower Canna (Cannaceae, Zingiberales)

Abstract: The asymmetric flower, lacking any plane of symmetry, is rare among angiosperms. Canna indica L. has conspicuously asymmetric flowers resulting from the presence of a half-fertile stamen, while the other androecial members develop as petaloid staminodes or abort early during development. The molecular basis of the asymmetric distribution of fertility and petaloidy in the androecial whorls remains unknown. Ontogenetic studies have shown that Canna flowers are borne on monochasial (cincinnus) partial florescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…To date, there have been only a few studies on CYC -like genes in other angiosperm families. These investigations have indicated the genes are primarily expressed in floral organs and affect the establishment of floral symmetry and stamen fertility [ 138 , 139 , 140 , 141 , 142 ]. Thus future research needs to be extended to these less-studied plant families.…”
Section: Progress In Research On Cyc -Like Genes I...mentioning
confidence: 99%
See 3 more Smart Citations
“…To date, there have been only a few studies on CYC -like genes in other angiosperm families. These investigations have indicated the genes are primarily expressed in floral organs and affect the establishment of floral symmetry and stamen fertility [ 138 , 139 , 140 , 141 , 142 ]. Thus future research needs to be extended to these less-studied plant families.…”
Section: Progress In Research On Cyc -Like Genes I...mentioning
confidence: 99%
“…Bartlett and Specht showed that gene replication unique to the Zingiberales , including one replication event involving the ECE clade gene TBL , preceded the diversification of commelinid monocotyledons [ 142 ]. The changes in TBL expression were associated with the evolutionary changes in floral symmetry and stamen abortion.…”
Section: Progress In Research On Cyc -Like Genes I...mentioning
confidence: 99%
See 2 more Smart Citations